Wives' and Husbands' Cortisol Reactivity to Proximal and Distal Dimensions of Couple Conflict. Issue 3 (3rd July 2013) - Rodriguez, Aubrey J.; Margolin, Gayla
<x xml:space="preserve">Abstract</x> Poor marital quality has been linked repeatedly to spouses' health problems, with alterations to physiological stress response systems, such as the hypothalamic‐pituitary‐adrenocortical (HPA) axis, as one putative mechanism. This study assessed wives' and husbands' HPA axis (i.e., cortisol) reactivity to marital criticism during laboratory‐based conflict discussions, in the context of marital aggression experienced during the previous year. Ninety‐five couples provided one saliva sample prior to—and three samples following—a triadic family conflict discussion involving their teenage child. Marital criticism during the conflict discussion was related to heightened HPA reactivity for husbands only. For wives, an interaction emerged between criticism during the conflict and previous‐year marital aggression: only those wives who had experienced high levels of marital aggression demonstrated a positive association between criticism and cortisol output. Husbands thus appeared to be more physiologically reactive to the in‐the‐moment critical behaviors, whereas wives' responses to proximal conflict were related to previous and perhaps more chronic experiences of marital aggression. These findings shed light on ways in which within‐couple processes during family conflicts involving children contribute to individual physiological functioning, enhancing our understanding of the role of family relationships in physical health outcomes.